Performance Review of Prefabricated Building Systems and Future Research in Australia - Satheeskumar Navaratnam; Tuan Ngo; Tharaka Gunawardena; David Henderson (Buildings, 2019)
Volumetric prefabricated building construction is growing in most developed countries; for example, in Sweden the market share of prefabricated building systems in the housing industry was more than 80%. However, in Australia only approximately 3⁻4% of new building constructions are prefabricated buildings in a year. A major hindrance to the growth of prefab construction in Australia is that systems are developed under commercial and confidential conditions. There are limited publicly-available research and case studies for certifiers, regulators, engineers and academia to provide independent information on the performance, advantages and disadvantages of prefabricated building systems. Independent designers and structural engineers are relying on the strength of the structural and non-structural element, as well as the connections of the prefabricated building systems. This strength is estimated from the “commercial-in-confidence„ test of individual components by manufactures, and it might result in undesired outcomes in design. This paper provides an overview of available literature on structural performance, benefits, constraints and challenges of prefabricated building systems. This paper also highlights the research needed on the prefabricated building systems such as full-scale tests, numerical modelling, hybrid simulations, case studies and social and economic assessments. Being supported by sound academic research will increase the market demand for prefabricated building systems in Australia as well as in other countries.